Prevalence of asthma and association with the allergic rhinitis among the patients attending a tertiary care hospital of district Varanasi: a cross sectional study - Singh, Raj Kamal (International Journal of Research in Medical Sciences, 2019)
Background: The prevalence of Bronchial Asthma and Allergic Rhinitis is increasing not only in developing countries but also in developed as well. These two has been the subject of several epidemiological investigations and found an overlapping of symptoms between both diseases. Methods: Present study conducted on the patients attending the OPD of Department of TB and chest, Institute of Medical Sciences, Banaras Hindu University, Varanasi and confirmed diagnosis of asthma and allergic rhinitis were made using spirometry and nasal-endoscopy respectively. Results: 110 participants of age between 15 to more than 56 years were included attending the OPD of Department of TB and Chest with signs and symptoms related to the asthma. 32(29.09%) participants were age group of 15-25 years, 34(30.09%) of 26-35 years,18(16.36%) of 36-45 years and 15(14%) participants were from age group of 46-55years and rest 11(9%) were of 56years and above. common symptom was found nasal discharge 62(79.48%) participants followed by headache which was there in 59(75.64%) participants, excessive sneezing was found in 54(69.23%) participants and facial, postnasal discharge was found in 48(61.53%) of participants .Only 6(5.45%) participants had confirmed asthma. 6 asthmatic participants undergone the nasal endoscopy and out of 6(100%), 4(66.66%) had confirmed the diagnosis of allergic rhinitis but association was not found statistically significant. Conclusions: The prevalence of bronchial asthma was higher among the younger age group Due to the overlapping of the symptoms between asthma and allergic rhinitis confirmatory diagnostic tools should be used before starting the treatment.